An Examination into the Portrayal of Deaf Characters and Deaf Issues in Picture Books for Children - Brittain, Isabel (Disability Studies Quarterly, 2004)
This paper examines children's picture books that either feature deaf characters or are aimed at a deaf audience. It is drawn from my Master's thesis An Examination into the Portrayal of Deaf Characters and Deaf Issues in Books for Children (2003), which examined 14primary texts that either feature deaf characters or are aimed at a deaf audience of young readers, those in later childhood and books for adolescents. My observations of books for the youngest readers are presented here. Two types of picture book are considered: those aimed at providing information about what it means to be deaf and those using a combination of pictures, sign symbols and words to tell a story. The methodology arises from two main critical perspectives. The first is Appleyard's theory of the needs of the reader in progressive stages of reader development and the second is based on a summary of the issues that surround the portrayal of "disability". My thesis acknowledges the political, social and cultural issues surrounding definitions of disability and looks at disability as a social rather than a medical issue. It also acknowledges the difference between having a hearing impairment and being part of Deaf culture. My analysis shows that those books that are most successful are shaped by the visual aspect of deaf culture and that these also reflect the narrative desires of the child reader as identified by Appleyard.